Analisis Pengaruh Employee Engagement, Emotional Intelligence, dan Komitmen terhadap Organizational Citizenship Behavior (OCB) pada Karyawan PO Efisiensi Cabang Kebumen - Much. Riyadus Solichin (Politeknik Sawunggalih Aji, 2018)
The purpose of this study is to examine the effects of emotional intelligence, employee engagement, and commitmentto organizational citizenship behavior (OCB) either partially or simultaneously on the employees of PO. Efficiency inKebumen with sample of the research are 47 employees. The sampling technique in this study used populationsamples. Analyzer used in this research by using multiple regression analysis and data processed with statistic toolSPPS 23.0. The results showed that emotional intelligence and employee engagement variables partially significanteffect on organizational citizenship behavior, it shows that testing hypothesis one and hypothesis two resultsaccepted. While for the commitment variable has no effect on the organizational citizenship behavior, it shows fortesting the third hypothesis is rejected. While the test results simultaneously the results of the fourth hypothesis testingshowed acceptable.